2022
DOI: 10.3390/ijms23031486
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Emissions of the Greenhouse Gas Nitrous Oxide by the Soybean Endosymbiont Bradyrhizobium diazoefficiens

Abstract: The greenhouse gas nitrous oxide (N2O) has strong potential to drive climate change. Soils are a major source of N2O, with microbial nitrification and denitrification being the primary processes involved in such emissions. The soybean endosymbiont Bradyrhizobium diazoefficiens is a model microorganism to study denitrification, a process that depends on a set of reductases, encoded by the napEDABC, nirK, norCBQD, and nosRZDYFLX genes, which sequentially reduce nitrate (NO3−) to nitrite (NO2−), nitric oxide (NO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Expression of the hao gene may not be subjected to O 2 repression, as NO could be generated by HAO under anerobic or aerobic conditions [36], although evidence is not available at present. In addition to O 2 , the key NOx in denitrification and dissimilatory NO 3 − reduction, and environmental factors such as pH, and various metals (Mo, Fe, or Cu) that function as cofactors, have all been shown to influence expression of genes in these pathways [143][144][145][146][147]. The major regulators mediating responses to O 2 and NOx belong to the cyclic AMP receptor protein (CRP)/fumarate and nitrate reductase regulation (FNR) superfamily, all referring to the same type of regulatory protein with similar domain structures.…”
Section: Regulation Of No Production In Bacteria 61 Regulation Of No ...mentioning
confidence: 99%
“…Expression of the hao gene may not be subjected to O 2 repression, as NO could be generated by HAO under anerobic or aerobic conditions [36], although evidence is not available at present. In addition to O 2 , the key NOx in denitrification and dissimilatory NO 3 − reduction, and environmental factors such as pH, and various metals (Mo, Fe, or Cu) that function as cofactors, have all been shown to influence expression of genes in these pathways [143][144][145][146][147]. The major regulators mediating responses to O 2 and NOx belong to the cyclic AMP receptor protein (CRP)/fumarate and nitrate reductase regulation (FNR) superfamily, all referring to the same type of regulatory protein with similar domain structures.…”
Section: Regulation Of No Production In Bacteria 61 Regulation Of No ...mentioning
confidence: 99%
“…Parejo and co-workers describe a fine-tuning modulation of oxidation-mediated posttranslational control of the FixK 2 factor in vivo [6]. Bueno and coworkers reported that FixK 2 and NnrR are regulatory determinants essential for denitrification in this bacterium [7]. Furthermore, the authors demonstrate that N 2 O reduction by B. diazoefficiens is independent of canonical inducers of denitrification, as the nitrogen oxide NO 3 − , and it is negatively affected by extreme values of pH (both acidic and alkaline conditions).…”
mentioning
confidence: 99%